2013
DOI: 10.13080/z-a.2013.100.051
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of spread and control of cercospora (Cercospora beticola Sacc.) and ramularia (Ramularia beticola Fautrey and F.Lamb.) leaf spot in sugar beet crops

Abstract: Dynamics of spread of the most destructive sugar beet foliar diseases cercospora (Cercospora beticola Sacc.) and ramularia (Ramularia beticola Fautrey & F.Lamb.) leaf spot and efficacy of six fungicides used for their control were investigated at Rumokai Research Station of Lithuanian Research Centre for Agriculture and Forestry during 2011-2012. The crop was sprayed with fungicides once after the first symptoms of foliar diseases had been spotted. In the experimental years, cercospora leaf spot started to spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The amplification of this advantageous fungus through the administration of small peptides could potentially suppress pathogen infection and support healthy plant growth and development [ 26 ]. Conversely, although no studies have directly shown that Ramularia can cause tea plant diseases, studies have shown that Ramularia can cause diseases in many plants, including but not limited to barley, beets and strawberries [ 27 , 28 ]. Therefore, this risk can be given due attention when using small peptides as foliar fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification of this advantageous fungus through the administration of small peptides could potentially suppress pathogen infection and support healthy plant growth and development [ 26 ]. Conversely, although no studies have directly shown that Ramularia can cause tea plant diseases, studies have shown that Ramularia can cause diseases in many plants, including but not limited to barley, beets and strawberries [ 27 , 28 ]. Therefore, this risk can be given due attention when using small peptides as foliar fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…In integrated protection, after using non-chemical methods and treatments, foliar fungicides are also applied [37,38]. These preparations, properly selected and applied in accordance with the principles of good agricultural practice, improve the health of plants and reduce losses caused by diseases [39,40]. Their use in their own study area was justified.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of the disease severity were done three times on the 1 st of August (before fungicide application), on the 1 st of September (a month after the first fungicide application) and on the 1 st of October (a month after the second fungicide application). Disease severity was estimated by establishing the diseaseaffected leaf area in per cent according to the scale: 0, 1, 2, 5, 10, 25, 35, 45 and 60 (EPPO Standards, 2004;Baltaduonytė et al, 2013). The disease severity (R) was calculated according to the formula:…”
Section: Methodsmentioning
confidence: 99%
“…where a is disease severity in the control treatment, b -disease severity in the fungicide applied treatment (Baltaduonytė et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation